Flags of convenience: legal responses to a 20th century shipping phenomenon - Hagenmeier, Cornelius (Institute of Marine and Environmental Law, 2023)
1999 a global tour of the International Transport Worker's Federation (ITF) vessel Global Mariner marked the 50th anniversary of the ITF's campaign against flags of convenience. For the second half of the 20th century this phenomenon has been subject both to constant public debate and to legal scrutiny. Generally, public opinion associates flags of convenience with ships owned by unscrupulous individuals from rich countries which are flagged out to certain developing countries in order to take advantage of a cheap work force and lesser safety standards.